CT Angiography Assessment of Dorsal Pancreatic Artery and Intrapancreatic Arcade Anatomy: Impact on Whipple Surgery Outcomes - Gorkem Ozdemir; Tolga Olmez; Okan Dilek; Berkay Eyi; Alper Sozutek; Ahmet Seker (Tomography)
Background/Objectives: The aim was to investigate the association between variations in the dorsal pancreatic artery (DPA) and intrapancreatic arcade anatomy with Whipple procedure outcomes and postoperative complications. Methods: This retrospective study was conducted with 362 patients who underwent a Whipple procedure at the Department of Gastroenterological Surgery of Adana City Training and Research Hospital between January 2018 and April 2024. All data collected from medical records were compared and statistically analyzed according to the patients’ survival status and arcade subtypes. Results: After excluding cases that did not meet the study criteria, a total of 284 patients were included in the study. DPA was visualized in 55.98% (159/284) of patients, while the intrapancreatic arcade was observed in 25% (71/284). The most common origin of the DPA was the splenic artery in 69.2% (n = 110) of patients, followed by the superior mesenteric artery in 17.6% (n = 28). The frequency of intrapancreatic arcade anatomy variations was as follows: type 1: 28.2% (n = 20), type 2: 49.3% (n = 35) and type 3: 22.5% (n = 16). Arcade type 4 anatomy was not detected. Postoperative pancreatic fistula (POPF) complication was found to be statistically significantly higher in patients with type 3 anatomy (p = 0.042). The 90-day mortality and long-term mortality rates did not differ among the groups based on the variations in both DPA and intrapancreatic arcade anatomy types. Conclusions: Patients with intrapancreatic arcade type 3 anatomy had a higher risk of POPF complications. Determination of preoperative arcade type by computed tomography (CT) angiography may help to predict the risk of POPF.